ANALISIS KEMAMPUAN INDIKATOR ANALISIS TEKNIKAL MOVING AVERAGE CONVERGENCE DIVERGENCE (MACD) DAN RELATIVE STRENGTH INDEX (RSI) DALAM MEMPREDIKSI PERGERAKAN HARGA SAHAM PADA KONDISI PASAR BULLISH DAN BEARISH DI BURSA EFEK INDONESIA (BEI) - admin, Richardo Rocha Gultom Richardo Rocha Gul Richardo Rocha Gultom B111112061 (Jurnal Manajemen Update, 2016)
This study aims to determine the ability of technical indicator analysis Moving Average Convergence Divergence (MACD) and Relative Strength Index (RSI) to predict the movements of stock prices of companies in bullish and bearish market conditions in Indonesian Stock Exchange (IDX). The Risk investment decision on the technical indicator MACD is done by looking at the intersection of the MACD line. While the RSI is done when the RSI line moves up from beneath the RSI of 30 or above 70 RSI that indicate oversold and overbought conditions of a stock. This research uses experimental design of within subject that puts each participant on more than one treatment. Number of participants are 30 participant. The sampling technique is purposive sampling. The tool of collection data bullish and bearish stock prices is Chartnexus application. The technique of analysis data used in this study is wilcoxon match pairs test. The results from this study showed that the indicators MACD and RSI are not able to predict the movement of stock prices in the bullish and bearish market conditions. For the accuracy prediction trend, MACD has the accuracy of 88 , 06% for bullish and 91.94% for bearish, RSI has the accuracy of 86.45% for bullish and 91.94% for bearish. From this research, investors can consider fundamental analysis to predict stock prices to assess the intrinsic value. Key Words : MACD, RSI, Technical Analisys, Bullish, Bearish, Trend, Stock Price Prediction. Â